2022
DOI: 10.1021/acs.cgd.2c00322
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogen and Hydrogen Bonds at the Periphery of Arylhydrazone Metal Complexes

Abstract: Ligands comprising an intramolecular resonance-assisted hydrogen bond (RAHB) and an intramolecular resonance-assisted chalcogen bond (RAChB) have been used to form Cu­(II), Ag­(I), and Cd­(II) metal complexes. Both interactions undergo major changes on ligand binding to the metal even though metal–ligand binding does not directly involve either interactions. In fact, the RAChB synthon can act as an intermolecular H-bond donor or acceptor, is involved in intramolecular coordination-coupled proton transfer, or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The chalcogen bond (ChB) has been recently exploited as a supramolecular tool for crystal growth and design involving metal complexes as tectons. 8,19–21 In this work, we have demonstrated that the simple design of ligands with a ChB donor selenium centre can contribute to the molecular oxygen and one-pot nitrile activation in copper( ii )-mediated synthesis. The tetravalent selenium atom acts as a ChB donor towards coordinated halogen atoms (Cl or Br) in the secondary coordination sphere of copper( ii ) complexes (see 2 , 3 and 5 in Scheme 3 and Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The chalcogen bond (ChB) has been recently exploited as a supramolecular tool for crystal growth and design involving metal complexes as tectons. 8,19–21 In this work, we have demonstrated that the simple design of ligands with a ChB donor selenium centre can contribute to the molecular oxygen and one-pot nitrile activation in copper( ii )-mediated synthesis. The tetravalent selenium atom acts as a ChB donor towards coordinated halogen atoms (Cl or Br) in the secondary coordination sphere of copper( ii ) complexes (see 2 , 3 and 5 in Scheme 3 and Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Benzenesulfonamide derivatives AL56, AL106, AL107, AL109 (Figure 1A) AL34 and AL110 (Figure 1B) were synthesized as described in the Methods section. The purity of AL56, AL106, AL107, AL109 derivatives (>95%) were verified from the melting point, Nuclear Magnetic Resonance (NMR) spectrum, elemental analysis and mass spectrometry measurements as reported in [14,15]. The 1 H-NMR spectra of AL34 and AL110 in DMSO-d 6 , and CH=N is observed at 10.25 and 9.93 ppm, respectively.…”
Section: Benzenesulfonamide Derivatives' Interaction With Receptor Ty...mentioning
confidence: 96%
“…The results of QTAIM analysis are summarized in Tables 1 and 2 The QTAIM analysis demonstrates the presence of appropriate bond critical points (3, −1) for HB, XB and ChB in model supramolecular associates (Table 1). The low magnitude of the electron density, positive values of the Laplacian of electron density and zero or very close to zero positive energy density in these bond critical points (3, −1) and estimated strengths for appropriate short contacts are typical for such non-covalent interactions is similar chemical systems [38,41,[48][49][50][51]. The balance between the Lagrangian kinetic energy G(r) and potential energy density V(r) at the bond critical points (3, −1) corresponding for HB, XB and ChB in model supramolecular associates reveals that a covalent contribution is absent in these contacts (−G(r)/V(r) > 1) [52].…”
Section: Contactmentioning
confidence: 97%